RNA-binding proteins RBM20 and PTBP1 regulate the alternative splicing of FHOD3. (January 2019) - Lorenzi, P.; Sangalli, A.; Fochi, S.; Dal Molin, A.; Malerba, G.; Zipeto, D.; Romanelli, M.G.
Abstract: Regulation of alternative splicing events is an essential step required for the expression of functional cytoskeleton and sarcomere proteins in cardiomyocytes. About 3% of idiopathic dilated cardiomyopathy cases present mutations in the RNA binding protein RBM20, a tissue specific regulator of alternative splicing. Transcripts expressed preferentially in skeletal and cardiac muscle, including TTN, CAMK2D, LDB3, LMO7, PDLIM3, RTN4, and RYR2, are RBM20-dependent splice variants. In the present study, we investigated the RBM20 involvement in post-transcriptional regulation of splicing variants expressed by Formin homology 2 domain containing 3 ( FHOD3) gene. FHOD3 is a sarcomeric protein highly expressed in the cardiac tissue and required for the assembly of the contractile apparatus. Recently, FHOD3 mutations have been found associated with heart diseases. We identified novel FHOD 3 splicing variants differentially expressed in human tissues and provided evidences that FHOD3 transcripts are specific RBM20 and PTBP1 targets. Furthermore, we demonstrated that the expression of RBM20 and PTBP1 promoted the alternative shift, from inclusion to exclusion, of selected FHOD3 exons. These results indicate that RBM20 and PTBP1 play a role in the actin filament functional organization mediated by FHOD3 isoforms and suggest their possible involvement in heart diseases.